IgG4-Related Lymphadenopathy Mimicking Mediastinal Lymph Node Metastasis of Lung Cancer on 18F-FDG PET/CT - Ting-Chun Tseng; Hung-Pin Chan; Daniel Hueng-Yuan Shen; Chang-Chung Lin (Diagnostics)
We report a case of a 73-year-old man with minimally invasive lung adenocarcinoma, post-resection, evaluated with 18F-FDG PET/CT for suspected disease progression. Imaging showed increased FDG uptake in the right lower lung mass and systemic lymphadenopathy (mediastinal, supraclavicular, axillary, paraaortic, and iliac regions). The appearance of a stable lymph node and a clinical history of IgG4 lymphadenopathy suggested an inflammatory process, although malignancy in the lung mass and mediastinal nodes could not be excluded. Lobectomy confirmed the presence of lung adenocarcinoma, while radical lymph node dissection identified IgG4-related lymphadenopathy without metastasis. This case underscores the need for considering differential diagnosis of PET-positive lymphadenopathy, especially in patients with comorbid conditions that mimic or coexist with malignancy.